Optimal location of piezoelectric patches for active vibration control - Labanieh, Mohamad Fateh; Syed Mohamed Ali, Jaffar; Shaik Dawood, Mohd. Sultan Ibrahim (IOP Publishing, 2017)
Active vibration control has been used to suppress and bring the structure back to its equilibrium state in shorter time than the old passive vibration mechanism. The increase in the settling time will cause the structure to face more internal forces and shear stress that will affect the life of the structure and reduce its reliability. This issue rises especially in the case of structures that are hard to maintain. Composite materials are also in high demand due to their excellent specific stiffness compared to the ordinary isotropic materials. Classical optimization method was selected to achieve the objective of this work. The focus of this study is to suppress the first natural frequency when excited by external force. The excitation of the plate was done through applying a force at the free edge and allowing the plate to settle under the influence of the active vibration control mechanism. Placing the piezo patches at the optimal location has decreased the settling time by 40% compared to the placing it at the centre of the fixed edge.